LEGAL PROTECTION OF PATIENT MEDICAL RECORDS IN INDONESIA IN REALIZED LEGAL CERTAINTY: English - Angga Perwira; Prassetyo Edi (Siber Nusantara of Law and Politic Review, 2026)
Medical records are documents containing confidential patient health information and therefore require legal protection. Digitization through electronic medical records has improved the quality of healthcare services, but has also given rise to various legal issues, particularly regarding the protection of patient personal data. Although Indonesia has regulations through Law Number 17 of 2023 concerning Health, Law Number 27 of 2022 concerning Personal Data Protection, Regulation of the Minister of Health Number 24 of 2022 concerning Medical Records, and the Law on Information and Electronic Transactions, these regulations are not yet fully harmonized, thus potentially creating legal uncertainty in the protection of patient medical records. The problems of this research are: (1) how are the regulations for legal protection of patient medical records according to laws and regulations in Indonesia; (2) what form of disharmony exists between the regulations for legal protection of patient medical records between the Health Law, the Law on Personal Data Protection, the Regulation of the Minister of Health on Medical Records, and the Law on Information and Electronic Transactions; and (3) how efforts to harmonize regulations for legal protection of patient medical records can achieve legal certainty in Indonesia. This research is a normative legal study that examines legal norms, legal principles, synchronization of laws and regulations, and legal harmonization through legislative, conceptual, comparative, and analytical approaches. The results of the study indicate that legal protection for patient medical records has been regulated in various laws and regulations. However, there is still disharmony in regulations related to the status of data controllers, patient rights, data protection mechanisms, legal accountability, and the imposition of sanctions, so that they do not fully provide legal certainty. Therefore, regulatory harmonization is needed through synchronization of content between regulations, strengthening personal data protection mechanisms, and affirming the authority and responsibilities of the parties to realize legal certainty in the protection of patient medical records in Indonesia.